Exploring Customer Satisfaction and Engagement in Café Culture: The Role of Intergenerational Interactions and Digital Engagement - Agrawal, Heit; Shah, Supan; Shah, Tanish; Bachani, Jenith; Chauhan, Rahul; Maseleno, Andino (Siber Journal of Advanced Multidisciplinary, 2025)
This study investigates the experiences and satisfaction levels of café-goers in Ahmedabad, focusing on the impact of intergenerational interactions, digital engagement, and cultural inclusivity on customer preferences and revisit intentions among younger consumers aged 18 to 35. Data were collected from 100 respondents using a structured questionnaire that addressed key factors such as service quality, ambiance, and overall social reinforcement. Regression analysis revealed no significant relationships between the independent variables and the purpose of visiting cafés, indicating the complexity of factors influencing customer behavior. The findings suggest the need for further exploration of additional variables to capture the intricacies of customer satisfaction. This research contributes to understanding the evolving café culture and its implications for enhancing customer experiences in public spaces.